Kajian Penambahan Bubuk Kayu Manis dengan Berbagai Tingkat Penyangraian Terhadap Mutu Fisik dan Organoleptik Kopi Robusta Celup Desa Lenangguar, Sumbawa - Afgani, Chairul Anam; Nurrahman, Aulia; Ariskanopitasari, Ariskanopitasari; Tanggasari, Devi (Pro Food, 2025)
Sumbawa Island is one of the coffee-producing areas that is marketed in various forms, one of which is dipped coffee. This dipping coffee consists of ground coffee and spices as flavor enhancers and is packaged in small paper bags to facilitate brewing. This study was conducted to determine the effect of cinnamon powder concentration and roasting time on the physical and organoleptic quality and typical dipped coffee of Lenangguar Village, Sumbawa. This study used a Completely Randomized Design with 2 factors: (1) roasting degree (light roast 8 minutes, medium roast 9 minutes, and dark roast 10 minutes), and (2) cinnamon powder concentration (3%, 5%, and 7%). The results showed that cinnamon powder concentration had a significant effect on the juice content and the flavor and aroma likability of dipped coffee, but had no significant effect on the physical color and the color likability. Meanwhile, roasting time had a significant effect on the juice content, the brightness level of physical color, and the likability of aroma, flavor, and color of dipped coffee. The recommended treatment for dipped coffee is medium roasting (9 minutes) with the addition of 5% cinnamon powder, which produces a juice content value of 0.47%, color brightness of 33.2, oHue value of 46.9 (red), with the likeabilty of color of 3.2 (like), aroma of 2.4 (somewhat like), and flavor of 3.3 (like).